Desingularización de superficies casi ordinarias irreducibles - Paucar Rojas, Rina Roxana (2017)
The aim of this thesis is to describe the resolution (partial and strict) of irreducible quasi ordinary surfaces (algebroids), by Lipman's approach. To achieve our goal, we de ne to the quasi ordinary surfaces (algebroids) and describe their parametrization by quasi ordinary branches, we also de ne the quasi ordinary rings, local rings of the quasi ordinary irreducible surfaces, and we study the relationship that exists between the tangent cone and singular locus of a quasi ordinary ring (invariants that appear in these resolutions) and the distinguished pairs of a quasi ordinary normalized branch that represents this ring. Also, we de ne the special transforms of a quasi ordinary ring and show that they are again quasi ordinary. We conclude with an example of these resolutions.